Healthcare professionals’ views for the content of the teddy bear hospital for a child sexual abuse prevention module - Abdul Rashid, Aneesa; Cheong, Ai Theng; Shamsuddin, Nurainul Hana; Roslan, Dalila; Shunmugam, Ranita Hisham (Taylor and Francis, 2021)
Worldwide studies have reported a drastic increase in child sexual abuse (CSA) involving very young children. In Malaysia, several attempts have been made to combat this problem via educational programs. Teachers have reported a lack of confidence in teaching this topic; hence a less threatening approach is needed. The Teddy Bear Hospital (TBH) is an innovation whereby the children bring their teddies while visiting the volunteers assuming healthcare practitioners’ role. This execution is effective in reducing the children’s anxieties about hospitalization and increasing their health knowledge. Therefore, our objective is to explore healthcare practitioners’ (HCP) views for the content of TBH and its approach as a personal safety module toward preventing CSA. Eighteen in-depth-interviews were conducted. Interviews were thematically analyzed. Participants suggest the TBH method as a good approach to teaching prevention of CSA among preschoolers. Four main themes emerged from this study: (1) educating children about personal safety, (2) moral values and faith as a medium to prevent child sexual abuse, (3) addressing social media use in children, and (4) general approach to content delivery. The involvement of parents is crucial. Addressing moral values and faith and usage of social media platforms are also essential factors to look into.